Peningkatan hasil belajar tolak peluru dengan media komet peluru whatsapp dan email (kopel wae) - Sendang Sri Widiastuti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The purpose of this study is 1). To find out the use of Kopel Wae media inthe learning of shot put on Class VII B students of SMP Negeri 2 Pakem. 2). Todescribe the improvement in learning outcomes of shot put using the Kopel Wae mediafor Class VII B students of SMP Negeri 2 Pakem. This research is a Classroom ActionResearch consisting of two cycles. Each cycle consists of planning, action, observationand reflection. The data in this study were taken from observation, evaluation, anddocumentation. Data were analyzed descriptively. Research results: 1). Cycle 1 gradeaverages 77.43. Cycle 2). The class average is 81.94. Based on these results it can beconcluded that the use of Kopel Wae Media in shot put learning can significantlyimprove the learning outcomes of Class VII B students of SMP Negeri 2 Pakem. Theincrease in learning outcomes is indicated by an increase in the average value of theclass from cycle 1 and cycle 2 by 4.51% and an increase in the number of studentscompleting learning from cycle 1 and cycle 2 by 18.75%.